Influence of paramagnetic melanin on the MRI contrast in melanoma: a combined high‐field (11.7 T) MRI and EPR study. (March 2014) - Godechal, Q.; Mignion, L.; Karroum, O.; Magat, J.; Danhier, P.; Morandini, R.; Ghanem, G. E.; Leveque, P.; Gallez, B.
<x xml:space="preserve">Abstract</x> Melanoma is the most dangerous form of skin cancer and its incidence is rising each year. Because the current methods of diagnosis based on the visual aspect of the tumor show limitations, several new techniques are emerging to help in this diagnosis, amongst which are magnetic resonance imaging (MRI) and electron paramagnetic resonance (EPR). The origin of the typical contrast pattern observable in melanoma in T1‐ and T2‐weighted images remains to be elucidated and is a source of controversy. In addition, melanin could create sufficient magnetic inhomogeneities to allow its visualization on T2*‐weighted images using high‐field MRI. In order to elucidate the possible role of melanin in the MRI contrast of melanoma, the present study was designed to correlate the paramagnetic content in melanin pigment to the contrast on T1‐, T2‐ and T2*‐weighted images. MR images were obtained in vivo at 11.7 T using four types of experimental tumors with different pigmentations (B16, HBL, LND1 melanomas and KHT sarcomas). The paramagnetic content in melanin pigment was measured by EPR. No significant correlation was observed between the content in melanin and the relaxation times T1, T2 and T2*, emphasizing that the presence of pigment alone has negligible effect on the MRI contrast. Copyright © 2014 John Wiley & Sons, Ltd.